Fragile resonance: caring for older family members in Japan and England - Chirinos, Carlos (Quaderns de l’Institut Català d’Antropologia, 2023)
Fragile resonance: caring for older family members in Japan and England Jason Danely (2022) New York, Cornell University Press 249 p. ISBN13: 9781501765810